Nisin J, a Novel Natural Nisin Variant, Is Produced by Staphylococcus capitis Sourced from the Human Skin Microbiota - O’Sullivan, Julie N. (J Bacteriol, 2020)
The skin microbiota is thought to play a key role in host protection from infection. Nisin J is a novel nisin variant produced by Staphylococcus capitis APC 2923, a strain isolated from the toe web space area in a screening study performed on the human skin microbiota. Whole-genome sequencing and mass spectrometry of the purified peptide confirmed that S. capitis APC 2923 produces a 3,458-Da bacteriocin, designated nisin J, which exhibited antimicrobial activity against a range of Gram-positive pathogens, including methicillin-resistant Staphylococcus aureus (MRSA) and Cutibacterium acnes. The gene order in the nisin J gene cluster (nsjFEGBTCJP) differs from that of other nisin variants in that it is lacking the nisin regulatory genes, nisRK, as well as the nisin immunity gene nisI. Nisin J has 9 amino acid changes compared to prototypical nisin A, with 8 amino acid substitutions, 6 of which are not present in other nisin variants (Ile4Lys, Met17Gln, Gly18Thr, Asn20Phe, Met21Ala, Ile30Gly, Val33His, and Lys34Thr), and an extra amino acid close to the C terminus, rendering nisin J the only nisin variant to contain 35 amino acids. This is the first report of a nisin variant produced by a Staphylococcus species and the first nisin producer isolated from human skin. IMPORTANCE This study describes the characterization of nisin J, the first example of a natural nisin variant, produced by a human skin isolate of staphylococcal origin. Nisin J displays inhibitory activity against a wide range of bacterial targets, including MRSA. This work demonstrates the potential of human commensals as a source for novel antimicrobials that could form part of the solution to antibiotic resistance across a broad range of bacterial pathogens.